2022
DOI: 10.1097/mbc.0000000000001128
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of factor Xa inhibitors associated intracranial haemorrhage at a tertiary medical centre

Abstract: Prior to the approval of andexanet, there were no FDA-approved reversal agents indicated for the treatment of factor Xa inhibitor (FXaI) associated major bleed. Four-factor prothrombin complex concentrate (4F-PCC) has been widely used off-label for FXaI-associated bleeding. The purpose of this study was to compare the effectiveness and safety of andexanet and 4F-PCC for the reversal of FXaI-associated intracranial haemorrhage. The primary end point is in-hospital mortality; secondary endpoints include haemosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…After the exclusion of these 2 studies, the data on the comparison of 4F-PCC and AA were derived from 8 retrospective studies. [35][36][37][39][40][41][42]44 We found that 4F-PCC had a comparable proportion of successful…”
Section: Subanalysismentioning
confidence: 61%
See 4 more Smart Citations
“…After the exclusion of these 2 studies, the data on the comparison of 4F-PCC and AA were derived from 8 retrospective studies. [35][36][37][39][40][41][42]44 We found that 4F-PCC had a comparable proportion of successful…”
Section: Subanalysismentioning
confidence: 61%
“…Several other smaller studies have shown the use of 4F-PCCs as a viable reversal option for DOAC-related ICH for anticoagulation reversal (reversal rates, 54.5%-94.7%) and safety (mortality rates, 4.7%-63.6%; thrombotic event rate, 0%-17.2%). 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 Albeit with significant heterogeneity, our meta-analysis found a combined proportion of anticoagulation reversed of 77%, a mortality rate of 26%, and a thromboembolic event rate of 8% ( Figures 1 - 3 ).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations